Peppa Goes Boating / Peppa's New Neighbours - Mandy Archer
A fantastic 2 in 1 Peppa Pig book set including 'Peppa Goes Boating' and 'Peppa's New Neighbours'. Peppa Goes Boating - Peppa and her family are ready to have fun on the water. Canoes, sailing boats and pedalos - everyone loves boating on the lake! Peppa's New Neighbours - Daddy Pig and Mr Bull are building a house. All it needs is a finishing touch from Peppa and it's ready! Will the new neighbours be pleased A brilliant selection of stories for young Peppa Pig fans to enjoy.